Evaluation Of The Level Of Passenger Satisfaction With Service At The Port Of Kayangan Crossing Of East Lombok Regency Of West Nusa Tenggara Province - Sri Kartini; Oktrianti Diani; Lalu Ahmad Mariadi (IWTJ : International Water Transport Journal, 2022)
The Kayangan Ferry Port is located in Labuhan Lombok Village, Pringgabaya District, East Lombok Regency, West Nusa Tenggara Province. Kayangan Ferry Port is a ferry port organized by the Transportation Service of West Nusa Tenggara Province. The Kayangan Ferry Port serves only one route, namely the Kayangan – Poto Tano route. The Kayangan Ferry Port has a very important role in improving the economy in East Lombok Regency, especially West Nusa Tenggara Province. Based on the results of the survey in the field, it was found that several services for passengers had not been carried out properly, such as health facilities with inadequate equipment, no gangway facilities, no information service facilities such as information and visual service desks, baggage/porter officers did not use uniforms and there are no facilities for disabled/handicapped passengers and room for breastfeeding mothers. In this study, the method used to analyze existing problems is the Customer Statisfaction Index, and Importance Performance Analysis. Based on the results of the analysis, it was found that the passenger satisfaction index of 64.9% of the service attributes were in quadrant I which had to be improved and improved in quality.